Pelatihan Penulisan Informasi Ruang Publik Melalui Eksplorasi Lanskap Linguistik Rumah Ibadah dan Lingkungan di Pura Buana Agung Kota Bontang - Utomo, Aries; Putra, Agus Kastama; Satria, Ridho Pratama (Alamtana: Jurnal Pengabdian Masyarakat UNW Mataram, 2025)
This community service activity took the form of training in writing public space information through an exploration of the linguistic landscape of houses of worship and the environment at Pura Buana Agung, Bontang City. Mistakes were often found in the writing of information on information boards, both in the form of words and grammar used. The solution offered was to provide assistance in the form of information writing training through exploration activities in the house of worship environment. This activity used lecture, discussion, and practice methods. Based on the results of the activities carried out, participants participated very well and were able to provide additional contributions to writing information in public spaces. In addition, the public information boards found around Pura Buana Agung were predominantly in Indonesian compared to foreign or regional languages. It is recommended that further training be provided periodically for the sustainability and development of the program in writing information in public spaces, especially in houses of worship and the environment of Pura Buana Agung, Bontang City.